2018
DOI: 10.2134/jeq2017.02.0084
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of Eddy Covariance to Estimate Methane Emissions from Grazing Cattle

Abstract: Grazing systems represent a significant source of enteric methane (CH), but available techniques for quantifying herd scale emissions are limited. This study explores the capability of an eddy covariance (EC) measurement system for long-term monitoring of CH emissions from grazing cattle. Measurements were made in two pasture settings: in the center of a large grazing paddock, and near a watering point where animals congregated during the day. Cattle positions were monitored through time-lapse images, and this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Supplemental hay was made available to the bison approximately 50 m west of the tower, and increases in the frequency of bison appearance there are associated with the animals' preferred feeding times after dawn and before dusk, but observed methane flux did not vary as a function of time of day (e.g., Dengel et al, 2011) as noted above. Regardless, ruminant methane flux measurements are simpler to make when animals congregate (Coates et al, 2017;Tallec et al, 2012) as was often observed in our study (e.g.,Figs. 2,9 and 10).…”
Section: Bison Spatial Distribution and Measurement Uncertaintymentioning
confidence: 52%
“…Supplemental hay was made available to the bison approximately 50 m west of the tower, and increases in the frequency of bison appearance there are associated with the animals' preferred feeding times after dawn and before dusk, but observed methane flux did not vary as a function of time of day (e.g., Dengel et al, 2011) as noted above. Regardless, ruminant methane flux measurements are simpler to make when animals congregate (Coates et al, 2017;Tallec et al, 2012) as was often observed in our study (e.g.,Figs. 2,9 and 10).…”
Section: Bison Spatial Distribution and Measurement Uncertaintymentioning
confidence: 52%
“…when animals congregate (Coates et al, 2017;Tallec et al, 2012) and ruminant behavior is critical to track to estimate fieldscale efflux (de la Motte et al, 2019). Aggregation behavior in our study bison herd was often upwind of the eddy covariance tower (Figures 6 & 11) and resulted in more overlap between flux footprint and bison location than would have occurred if bison locations were randomly distributed throughout the study area, emphasizing the importance of tower placement in studies of grazing systems.…”
Section: Bison Spatial Distributionmentioning
confidence: 80%
“…The application of the EC technique to quantify CH 4 fluxes and other tracer gases was made possible with the development of fast-response and fielddeployable optical sensors [25]. The method requires the knowledge of animal numbers and their location within the footprint and a model to interpret the relationship between the calculated flux and the emission rate of point sources within the footprint [90]. Under the current technical conditions, minor fluctuations of air mass and energy flux on several time scales (hour, day, season, and year) can be measured [89].…”
Section: Eddy Covariance (Ec) Techniquementioning
confidence: 99%